Iptacopan for cold agglutinin disease: a case report with literature review - Fang, Baozhi; Lu, Hongbin; Yu, Xiao; Wang, Peng; Zhou, Yifei; Shen, Qiudan; Yuan, Muzhi; Lyu, Mingen; He, Guangsheng (Frontiers in Immunology, 2025)
This study reports a case of cold agglutinin disease (CAD) secondary to lymphoplasmacytic lymphoma in a patient intolerant to rituximab plus bendamustine and with persistent uncontrolled hemolysis following zanubrutinib therapy. The addition of the complement C3 inhibitor iptacopan to a cyclophosphamide and dexamethasone regimen successfully controlled hemolysis and improved hemoglobin levels. Within one week of treatment, the patient achieved transfusion independence, with hemoglobin increasing from 67 g/L to 90 g/L by week 3 and 101 g/L by week 7, alongside normalized bilirubin levels and no adverse events. The follow-up period was 4 months, during which the patient showed sustained remission. These findings suggest that iptacopan can rapidly ameliorate hemolysis in CAD, warranting further investigation into its therapeutic potential.